2021
DOI: 10.3390/fermentation7030183
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Autochthonous Non-Saccharomyces Yeasts by Sequential Fermentation for Wine Differentiation in Galicia (NW Spain)

Abstract: Non-Saccharomyces yeasts constitute a useful tool in winemaking because they secrete hydrolytic enzymes and produce metabolites that enhance wine quality; in addition, their ability to reduce alcohol content and/or to increase acidity can help to mitigate the effects of climatic change on wines. The purpose of this study was to evaluate the oenological traits of non-Saccharomyces yeast strains autochthonous from Galicia (NW Spain). To do that, we carried out sequential fermentation using 13 different species f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 74 publications
1
9
0
Order By: Relevance
“…Some authors have proposed different mechanisms in the relationships between S. cerevisiae and non-Saccharomyces [18,51,52]. In this sense, the NS+XG3 group showed the highest concentration of volatile compounds, which have confirmed that native strains can improve the chemical and sensory characteristics, and differentiation of wines in accordance with numerous recent studies [3,30,[53][54][55]. In contrast, compounds accounting for acidity in the biplot are concentrated in the area of NS+EC1118 wines.…”
Section: Selection Of Autochthonous Strains According To Their Oenolo...supporting
confidence: 76%
See 3 more Smart Citations
“…Some authors have proposed different mechanisms in the relationships between S. cerevisiae and non-Saccharomyces [18,51,52]. In this sense, the NS+XG3 group showed the highest concentration of volatile compounds, which have confirmed that native strains can improve the chemical and sensory characteristics, and differentiation of wines in accordance with numerous recent studies [3,30,[53][54][55]. In contrast, compounds accounting for acidity in the biplot are concentrated in the area of NS+EC1118 wines.…”
Section: Selection Of Autochthonous Strains According To Their Oenolo...supporting
confidence: 76%
“…4). These concentrations are lower than 300 mgꞏL −1 , above which the aromas become undesirable, although the wines from pure culture fermentations achieved lower content of higher alcohols than those obtained for the same strains tested in sequential fermentations [29,30]. In addition, all the yeast species evaluated produced lower concentrations of these volatiles in the wines than S. cerevisiae, being L. thermotolerans the non-Saccharomyces species that produced the highest concentration of higher alcohols, in some cases doubling the concentration generated by Starm.…”
Section: Chemical Analysesmentioning
confidence: 80%
See 2 more Smart Citations
“…The sequential fermentation of M. pulcherrima B-5 with S. cerevisiae QA23 did not significantly affect the ethanol content in both processes with and without maceration. Although it is considered that M. pulcherrima can produce wines with low ethanol content [18], there are some reports in which this strain did not affect the ethanol content [32] and good fermentation potential of M. pulcherrima was stated [9]. This indicates that the ability of M. pulcherrima to reduce ethanol content can be strain-dependent [10].…”
Section: Discussionmentioning
confidence: 99%